Dental development in living and fossil orangutans. Issue 94 (May 2016) - Smith, Tanya M.
Abstract: Numerous studies have investigated molar development in extant and fossil hominoids, yet relatively little is known about orangutans, the only great ape with an extensive fossil record. This study characterizes aspects of dental development, including cuspal enamel daily secretion rate, long-period line periodicities, cusp-specific molar crown formation times and extension rates, and initiation and completion ages in living and fossil orangutan postcanine teeth. Daily secretion rate and periodicities in living orangutans are similar to previous reports, while crown formation times often exceed published values, although direct comparisons are limited. One wild Bornean individual died at 4.5 years of age with fully erupted first molars (M1s), while a captive individual and a wild Sumatran individual likely erupted their M1s around five or six years of age. These data underscore the need for additional samples of orangutans of known sex, species, and developmental environment to explore potential sources of variation in molar emergence and their relationship to life history variables. Fossil orangutans possess larger crowns than living orangutans, show similarities in periodicities, and have faster daily secretion rate, longer crown formation times, and slower extension rates. Molar crown formation times exceed reported values for other fossil apes, including Gigantopithecus blacki . When compared to African apes, both living and fossil orangutans show greater cuspal enamel thickness values and periodicities, resulting in longer crown formation times and slower extension rates. Several of these variables are similar to modern humans, representing examples of convergent evolution. Molar crown formation does not appear to be equivalent among extant great apes or consistent within living and fossil members of Pongo or Homo .